Comparing school-related risk factors of stereotypical bullying perpetration and cyberbullying perpetration - Bergmann, Marie Christine (European journal of criminology, 2022)
Based on the combination of two representative surveys of ninth graders (N = 20,150) conducted in 2013 and 2015 in Lower Saxony, Germany, this article first examines the prevalence of cyberbullying perpetration and stereotypical bullying perpetration. Second, in addition to already existing research, the prevalence of the simultaneous perpetration of stereotypical bullying and cyberbullying is presented here as well. In order to overcome the limitations of existing research, General Strain Theory (GST; Agnew, 1992) is used to theoretically determine why it is expected that school characteristics are associated with the three forms of bullying. In the students’ preceding semester, 6.1 percent of the surveyed adolescents were perpetrators of stereotypical bullying, 1.1 percent bullied someone online, and 1.3 percent of the juveniles engaged in both bullying behaviors. Binary logistic multilevel analyses show that school-related strains are in fact related to the perpetration of stereotypical bullying, cyberbullying, and the perpetration of both behaviors simultaneously. The risk of engaging in the perpetration of stereotypical bullying, and the perpetration of cyberbullying and stereotypical bullying simultaneously, is especially increased by school-related strains. Thus, those respondents who carry out bullying behaviors in the school context seem to be especially affected by school-related strains.